Emerging trends: Ethics, intimidation, and the Cold War. (May 2021) - Church, Kenneth Ward; Kordoni, Valia
Abstract: There are well-meaning efforts to address ethics that will likely make the world a better place, but care needs to be taken to avoid repeating mistakes of the past. In particular, ACL has recently introduced a new process where there are special reviews of some papers for ethics. We would be more comfortable with the new ethics process if there were more checks and balances, due process and transparency. Otherwise, there is a risk that the process could intimidate authors in ways that are not that dissimilar from the ways that academics were intimidated during the Cold War on both sides of the Iron Curtain.